EXPLORING THE PATHOMORPHOLOGICAL CHARACTERISTICS OF THE LUNGS IN POST-COVID SYNDROME: A COMPREHENSIVE REVIEW OF CURRENT EVIDENCE - Sheraliyev Ilyosjon Ibroxim oʻgʻli (American Journals, 2024)
The global COVID-19 pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to significant morbidity and mortality, with a rising body of literature documenting persistent symptoms and complications in individual’s post-infection, collectively referred to as post-COVID syndrome or long COVID. Among the myriad manifestations of this condition, respiratory complications have emerged as a critical area of investigation, highlighting the need for a comprehensive understanding of the pathomorphological changes occurring in lung tissue following infection. This review synthesizes current evidence regarding the pathomorphological characteristics of the lungs in post-COVID patients, revealing a spectrum of pulmonary sequelae, including chronic cough, dyspnea, and reduced pulmonary function. Histopathological findings such as interstitial inflammation, alveolar injury, and fibrosis underscore the potential for long-term respiratory complications. The review advocates for a multidisciplinary approach that integrates respiratory rehabilitation, psychological support, and pharmacological interventions to improve patient outcomes. Additionally, it identifies research gaps and emphasizes the necessity for longitudinal studies across diverse populations to further elucidate the enduring effects of COVID-19 on lung health. By addressing these pathomorphological characteristics, the review aims to inform targeted therapeutic strategies and enhance the quality of life for affected individuals.
Keywords: Post-COVID syndrome, SARS-CoV-2, lung pathology, pathomorphological changes, pulmonary complications, respiratory symptoms, interstitial inflammation, alveolar injury, fibrosis, multidisciplinary approach, patient outcomes.